Glyphosate: Human Exposure and Health Impacts — A Literature Review - Słojewska, Aleksandra; Łabuda, Mikołaj; Królikowska, Klaudia; Bogucka, Adrianna; Sowińska, Teresa; Mentel, Oliwia; Sikora, Jakub; Knychalska, Karolina; Kotkowiak, Agata; Szema, Agnieszka (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Glyphosate is the most widely used herbicide globally, primarily due to its effectiveness and compatibility with genetically modified (GM) crops. Its non-selective action on the shikimate pathway makes it suitable for widespread use in agriculture, urban areas, and water management. However, growing concerns have emerged over its potential health effects, particularly following its classification by IARC in 2015 as "probably carcinogenic to humans." This review aims to examine current knowledge on glyphosate exposure, its environmental prevalence, human biomonitoring data, and associated health risks. Brief Description of the State of Knowledge: Extensive global use of glyphosate has led to its detection in air, soil, water, and food. Urinary biomonitoring studies in the U.S. and Europe show high detection rates, with levels varying by region, age, and occupation. Although glyphosate alone exhibits low mammalian toxicity, commercial formulations (GBHs) often contain adjuvants that enhance toxicity. Health concerns include reproductive toxicity, carcinogenicity, gut microbiome disruption, and interference with embryonic development. Glyphosate’s action on gut bacteria and cytochrome P450 enzymes may contribute to conditions such as autism, autoimmune diseases, and developmental abnormalities. Conclusions: Widespread human exposure to glyphosate is now well-documented. Given its environmental persistence and health concerns, continued biomonitoring and independent research are critical. Future regulatory decisions should assess full GBH formulations, not just glyphosate alone, and consider cumulative effects. Enhancing reporting transparency, and improving public access to pesticide data are essential for protecting environmental and public health.